Profitability, Leverage, Corporate Social Responsibility, and Institutional Ownership: Determinants of Tax Aggressiveness in the Indonesian Capital Market, 2020–2023 - Yosida Isdianawati; Bobby Fisher (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Tax aggressiveness has emerged as a strategic concern due to its potential to erode state revenues through corporate practices aimed at minimizing tax obligations, whether by lawful tax planning or through more opaque, potentially unlawful strategies. This study examines the influence of profitability, leverage, corporate social responsibility (CSR), and institutional ownership on tax aggressiveness among firms in the basic and chemical industries listed on the Indonesia Stock Exchange (IDX) over the 2020–2023 period. Drawing on panel data from 132 firms, the analysis employs panel regression techniques to identify the relationships among these variables. The findings indicate that profitability, CSR, and leverage are significantly associated with tax aggressiveness, whereas institutional ownership does not exhibit a statistically significant effect.